Analisis Peran dan Fungsi Komite Sekolah Dalam Upaya Peningkatan Mutu Pendidikan SD Muhammadiyah 3 Pandaan - Muhamad Usamah Rasyidi (Jurnal Penelitian dan Pendidikan IPS, 2019)
In effort to improve the quality of education in community, school must be able to establish a good relationship with the surrounding community. This school (SD Muhammadiyah 3 Pandaan) is one of the educational institutions, which does not work alone in facing a problem, but SD Muhammadiyah 3 Pandaan inviting the School Committee as its working partner. The focus of the research is learning how the role and the function of school committee, the effectiveness of learning, school principal leadership, quality culture, the obstacles faced by school committee, and efforts to overcome the obstacles experienced by school committee of SD Muhammadiyah 3 Pandaan in efforts to improve the quality of education. The purpose of this research is to find out the role and function of school committee, learning effectiveness, leadership of school principals, quality culture, obstacles faced by school committee, and efforts to overcome obstacles experienced by school committee of SD Muhammadiyah 3 Pandaan in efforts to improve the quality of education. This research uses a qualitative method with the type of case study. Based on the results of research that the school committee is quite active in carrying out its role and function as a advisory agency, as a supporting agency, as a controlling agency, and as a mediator institution. The effectiveness of learning in SD Muhammadiyah 3 Pandaan is seen in exploratorial learning. The leadership of the Principal of Muhammadiyah 3 Pandaan Elementary School is good enough. The quality culture is reflected in “Kantin Sehat” and “Jum’at Bersih”. Some obstacle experienced are the member performance is not good enough, lack of training from the education office, lack of funding. Efforts in overcoming obstacles include: the establishment of POM (Paguyuban Orangtua Murid), a written proposal to the education office, and establishing a healthy canteen, a pick-up car, and membership fees.